Vertical transmission of coronavirus disease 2019: a systematic review and meta-analysis - Kotlyar, Alexander M.; Grechukhina, Olga; Chen, Alice; Popkhadze, Shota; Grimshaw, Alyssa; Tal, Oded; Taylor, Hugh S.; Tal, Reshef (American journal of obstetrics and gynecology, 2021)
This study aimed to conduct a systematic review of the current literature to determine estimates of vertical transmission of coronavirus disease 2019 based on early RNA detection of severe acute respiratory syndrome coronavirus 2 after birth from various neonatal or fetal sources and neonatal serology. Eligible studies published until May 28, 2020, were retrieved from PubMed, EMBASE, medRxiv, and bioRxiv collection databases. This systematic review included cohort studies, case series, and case reports of pregnant women who received a coronavirus disease 2019 diagnosis using severe acute respiratory syndrome coronavirus 2 viral RNA test and had reported data regarding the testing of neonates or fetuses for severe acute respiratory syndrome coronavirus 2 immediately after birth and within 48 hours of birth. A total of 30 eligible case reports describing 43 tested neonates and 38 cohort or case series studies describing 936 tested neonates were included. The methodological quality of all included studies was evaluated by a modified version of the Newcastle-Ottawa scale. Quantitative synthesis was performed on cohort or case series studies according to the neonatal biological specimen site to reach pooled proportions of vertical transmission. Our quantitative synthesis revealed that of 936 neonates from mothers with coronavirus disease 2019, 27 neonates had a positive result for severe acute respiratory syndrome coronavirus 2 viral RNA test using nasopharyngeal swab, indicating a pooled proportion of 3.2% (95% confidence interval, 2.2–4.3) for vertical transmission. Of note, the pooled proportion of severe acute respiratory syndrome coronavirus 2 positivity in neonates by nasopharyngeal swab in studies from China was 2.0% (8/397), which was similar to the pooled proportion of 2.7% (14/517) in studies from outside of China. Severe acute respiratory syndrome coronavirus 2 viral RNA testing in neonatal cord blood was positive in 2.9% of samples (1/34), 7.7% of placenta samples (2/26), 0% of amniotic fluid (0/51), 0% of urine samples (0/17), and 9.7% of fecal or rectal swabs (3/31). Neonatal serology was positive in 3 of 82 samples (3.7%) (based on the presence of immunoglobulin M). Vertical transmission of severe acute respiratory syndrome coronavirus 2 is possible and seems to occur in a minority of cases of maternal coronavirus disease 2019 infection in the third trimester. The rates of infection are similar to those of other pathogens that cause congenital infections. However, given the paucity of early trimester data, no assessment can yet be made regarding the rates of vertical transmission in early pregnancy and potential risk for consequent fetal morbidity and mortality.